(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Bituminous mix is a mixture of coarse aggregate, fine aggregate and filler. Hot Mix Asphalt (HMA) is a type of bituminous mix in which all particles are mixed and compacted at high degree of temperature. HMA is available in two forms namely dense graded and Stone Matrix Asphalt (SMA), formally is known as Bituminous Concrete (BC) and second one is known as gap graded. SMA needs additional fiber to minimize the drainage through the material. In this research, an effort has been made to enhance the stability of SMA by using banana fiber as a filler agent along with binder content (BC). The mixture has been prepared as per the MORTH specification. The grade of bitumen used in this research work is VG-30. The percentage of BC and fiber content is varied from 4.8 % to 6.4 % and from 0 % to 0.8 %. A number of tests have been performed on the marble dust to check its properties. As per the test analysis, Marble dust is used to find out Optimum Binder Content (OBC) and has been used for the mixture with an average value determined as 5.5 %. After adding 5.5 % of BC into the bitumen along with different percentage of banana fiber such as 0 %, 0.2 %, 0.4 %, 0.6 % and 0.8 %. The experiments has been performed on five different samples and tests values in terms of stability, flow value, Air Void (VA) and Void in Mineral Aggregate (VMA) have been measured. From the experiment it has been observed that banana fiber enhances the stability of the mixed sample.